2014
DOI: 10.1007/s11033-014-3097-6
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones association with depression severity and clinical outcome in patients with major depressive disorder

Abstract: The clinical implications of thyroid hormones in depression have been studied extensively and still remains disputable. Supplementation of thyroid hormones is considered to augment and accelerate antidepressant treatment. Studies on the role of thyroid hormones in depression deliver contradictory results. Here we assess theirs impact on depression severity and final clinical outcome in patients with major depression. Thyrotropin, free thyroxine (FT4), and free triiodothyronine (FT3) concentrations were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…The HPA axis pathways, which have rich neuroimmunological interactions, have gained recent attention, and dysregulation of the HPA axis can persist for several years after a stroke 32. Conversely, the HPT axis has received little attention in clinical and experimental studies of acute stroke, although anxiety may lead to thyroid abnormalities, in serum FT4 and FT3 33,34. In the present study, serum FT3 levels were decreased compared with the sham group.…”
Section: Discussionmentioning
confidence: 45%
“…The HPA axis pathways, which have rich neuroimmunological interactions, have gained recent attention, and dysregulation of the HPA axis can persist for several years after a stroke 32. Conversely, the HPT axis has received little attention in clinical and experimental studies of acute stroke, although anxiety may lead to thyroid abnormalities, in serum FT4 and FT3 33,34. In the present study, serum FT3 levels were decreased compared with the sham group.…”
Section: Discussionmentioning
confidence: 45%
“…A study conducted by Berent D and his associates on 44 patients found that the TSH serum level in patients with depression were within normal range. [16] In the instant study, TSH level was found decreased in the patients group (2.4914) as compared to control group (2.9350). [16] Association between depression and glycemic control in patients with type 2 diabetes mellitus was studied by José María De la Roca-Chiapas and his associates in 68 patients.…”
Section: Discussionmentioning
confidence: 80%
“…[16] In the instant study, TSH level was found decreased in the patients group (2.4914) as compared to control group (2.9350). [16] Association between depression and glycemic control in patients with type 2 diabetes mellitus was studied by José María De la Roca-Chiapas and his associates in 68 patients. They found that fasting glucose level was higher (175+-63.5) and their glycaemic control was also poor.…”
Section: Discussionmentioning
confidence: 80%
“…The incidence of hypothyroidism increases after 60 years, often ranging from 0.5% to 5% in cases of frank hypothyroidism and 15% to 20% in cases of subclinical hypothyroidism. Thyroid hormone concentrations are associated with the severity of depression and may have an impact on the final clinical outcome 26 .…”
Section: Discussionmentioning
confidence: 99%